A New African Orality? Tijānī Sufism, Sacred Knowledge and the ICTs in Post-Truth Times. - De-Diego-González, Antonio (Boydell & Brewer, 2021)
West Africa is a space of paradoxes. Not even the most traditional Sufis can resist information and communication technologies (ICT). Nowadays they carry the tasbīḥ (prayer beads) in one hand and, in the other, a mobile phone or an iPad of the latest generation, to help them transmit ancient knowledge. From this it seems that sacred knowledge (ma‘rifa) and technology are compatible since they make life easier for the Muslim community, as Ibrahim Niasse (1900–75) already pointed out in the 1950s. Shaykh Ibrahim has been a well-authorized voice. He himself founded the Fayḍa community in 1929, reviving Tijānī Sufism in West Africa, and adapting it to current times, while maintaining a great respect for the traditional episteme. Niasse not only lived during the beginnings of the technological revolution, but he also authorized the use of microphones, speakers, and recordings for the purpose of helping Muslims in their dīn. He was also a strong advocate of contemporaneity, which did not prevent him from being one of the greatest mystics of the twentieth century, and keeping Sufism in balance with Islamic law (sharī‘a). This testimony is illustrative of many things. The interviewee not only expresses how a Sufi master uses technology, but at the same time he emphasizes the transmission of baraka (subtle and beneficial energy) through the voice of the shaykh. Traditionally, the baraka was obtained in the presence of shaykhs and holy people, but today, as the testimony of this informant suggests, it can be conveyed through a telephone conversation. The physical presence of yesteryear is replaced by today's digital presence.
Es una versión de autoarchivo que sigue los protocolos que me han recomendado la propia editorial tras consultarles y remitirme a su página web: https://boydellandbrewer.com/rights-permissions/ Boydell & Brewer considers the following to be repository policy standard terms and conditions, but we are willing to consider further exceptions to this policy on a case-by-case basis when applied for by the author of the Work: Author Accepted Manuscript (AAM) version Embargo of at least 12 months Not-for-profit platform Closed repository not accessible wider than the community/institution unless institutional policy mandates otherwise Must have a clear citation and link to details of the published version on the Boydell & Brewer website Must have a disclaimer indicating the content may not be copied, deposited or reused
Keywords: Sufismo - África occidental - Historia; Islam; Sufismo; Epistemología; TIC; Tariqa Tijaniyya; Religión digital